2018
DOI: 10.1128/jcm.01322-17
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Bartonella henselae IgM Western Blot Bands for Serodiagnosis of Cat Scratch Disease

Abstract: We evaluated the utility of Western blot (WB) bands of e in detecting anti- immunoglobulin M (IgM) for serodiagnosis of cat scratch disease (CSD). IgM band patterns were examined using sera from 92 patients clinically suspected of having CSD and from 130 healthy individuals. Positive WB bands were observed in 49 (53.5%) of the 92 patient sera. Three bands at 8 to 10, 31 to 35, and 70 kDa were regarded as relevant for because all of the positive sera yielded at least one of the three bands, and none of the heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Alternatively, some IFA seronegative humans (control group) may have been exposed to a Bartonella spp., but immunofluorescence was not visualized using cell cultured Bartonella spp. antigens, as was previously reported (16). In the context of specificity, B. henselae Pap31 shares homology with Neisseria opacity proteins (Opa), Brucella OMP31 (a putative porin), and Agrobacterium tumefaciens OMP25 (an immunogenic surface protein) [29,30].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Alternatively, some IFA seronegative humans (control group) may have been exposed to a Bartonella spp., but immunofluorescence was not visualized using cell cultured Bartonella spp. antigens, as was previously reported (16). In the context of specificity, B. henselae Pap31 shares homology with Neisseria opacity proteins (Opa), Brucella OMP31 (a putative porin), and Agrobacterium tumefaciens OMP25 (an immunogenic surface protein) [29,30].…”
Section: Discussionsupporting
confidence: 69%
“…Currently, the diagnosis of canine and human Bartonelloses is performed by the isolation of Bartonella by culture, the amplification of Bartonella DNA by PCR, and the detection of Bartonella antibodies by serological assays. Although serology can only confirm exposure, immunofluorescent antibody assays (IFAs), Western Blot (WB), and enzyme-linked immunosorbent assays (ELISAs) are most frequently used for the diagnosis of canine and human Bartonelloses [11][12][13][14][15][16][17][18][19][20]. Previously, we reported that the sensitivity of IFA did not substantially improve despite using a panel consisting of eight Bartonella IFA antigens, each tested as an independent serological assay [21].…”
Section: Introductionmentioning
confidence: 99%
“…ELISA and Indirect immunoflourescence assays (IFA) are the standard tools to diagnose bartonellosis, however increased sensitivity is associated with decreased specificity with both these antibody assays [79,80]. There is preliminary evidence that Western blot testing for Bartonella as performed in this case series is both more sensitive and specific than either IFA or ELISA testing [81].…”
Section: Discussionmentioning
confidence: 81%
“…Western blotting (WB) has been used for the serodiagnosis of bartonelloses in humans; however, the utility of WB for the serodiagnosis of canine bartonelloses has not been critically investigated. A study investigating the utility of B. henselae WB using serum samples from 92 human patients clinically suspected of cat scratch disease (CSD) documented a higher sensitivity of WB (53.5%) than of IFA (28.3%) (12). Investigators reported a 100% sensitivity of WB when it was used to diagnose blood culture-negative endocarditis in humans (3).…”
mentioning
confidence: 99%